Development and Testing of a Test Rig for Coaxial Motor-Propeller Configurations - Wong, Qi En; Bin Wan Salim, Wan Saiful-Islam (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study focuses on the development and testing of a versatile test rig designed to evaluate coaxial motor-propeller systems crucial for UAVs and eVTOL aircraft. The rig includes a configurable mounting bracket assembly, connecting arms, an aluminium support frame, and accurately placed load cells, all connected via a universal mounting platform. Key components were 3D-printed using PETG for durability and weight efficiency, while aluminium profiles provided stability. The tests were carried out by varying propeller distance and tilt angle at different motor speeds to assess their impact on thrust. Findings indicate that increasing the distance between propellers initially boosts thrust, peaking at a 12 cm coaxial distance, after which thrust decreases due to diminished aerodynamic effectiveness. Increasing the tilt angle consistently enhances thrust, demonstrating its critical role in optimising performance. The results underscore that while both parameters are important, adjusting the tilt angle significantly improves thrust more than distance variations. This insight is valuable for designing efficient coaxial systems. Future research should further investigate the combined effects of distance and tilt angle to enhance system efficiency in aerospace applications.